Effects of soothing images and soothing sounds on mood and well‐being. (7th November 2022) - Witten, Emily; Ryynanen, Jasmiina; Wisdom, Stella; Tipp, Cheryl; Chan, Stella W. Y.
Abstract: Objectives: Mental health problems are increasing at an alarming rate, calling for the need for more cost‐effective and easily accessible interventions. Visual images and sounds depicting nature have been found to have positive effects on individuals' mood and well‐being; however, the combined effects of images and sounds have been scarcely investigated. This study therefore aimed to compare the mood effects of viewing nature‐related soothing images versus listening to soothing sounds versus a combination of both. Methods: In this study, 149 participants aged 18–83 years old ( M  = 35.88, SD  = 15.63; 72.5% female, male 26.8%, .7% transgender) were randomised into three intervention conditions: images only, sounds only or combined (images and sounds). Baseline depressive and anxiety symptoms were indexed, and four outcome variables (positive affect, negative affect, serenity affect and depressive mood states) were measured pre‐ and post‐intervention. Results: Findings showed that all participants, regardless of group, reported a decrease in negative affect, positive affect and depressive mood as well as an increase in serenity affect (including feelings of soothe). However, there were no group differences. Exploratory analyses found that individuals with higher levels of depressive and anxiety symptoms at baseline experienced greater reduction in negative affect and depressive mood state, as well as a larger increase in serenity affect. Conclusions: These findings therefore provide preliminary evidence that, upon further research and development, images and sounds depicting nature can potentially be developed for use as an effective tool to improve mood and well‐being.